The analysis of cannabinoids in cannabis samples by supercritical fluid chromatography and ultra‐high‐performance liquid chromatography: A comparison study. Issue 1 (26th November 2020) - Deidda, Riccardo; Schelling, Cédric; Roussel, Jean‐Marc; Dispas, Amandine; De Bleye, Charlotte; Ziemons, Éric; Hubert, Philippe; Veuthey, Jean‐Luc
Abstract: The aim of this work was to develop a supercritical fluid chromatographic method to study the applicability of this emerging technique to cannabinoid analysis and showcase its advantages. During method development, the authors focused on nine phyto‐cannabinoids to assess the selectivity needed to potentially perform the quantitation of each cannabinoid. After method development, robustness studies were carried out on this method to gain more information about its qualitative behavior (in terms of critical resolutions) when varying some crucial parameters (concentration of additive, column temperature, starting gradient conditions and column batch). Once the robustness was evaluated and the parameters most affecting the selected responses were individuated, the SFC method was applied for a simulated routine use to generate quantitative results concerning the concentrations of the main cannabinoids in real cannabis samples. The samples were also analyzed by means of an ultra‐high‐performance liquid chromatographic method currently used in the laboratory for the same objective. Finally, the results obtained with both analytical methods were compared to evaluate their accordance. The Bland–Altman method was applied as a statistical strategy to evaluate the degree of accordance between the results generated and display the data in a difference plot. The ultra‐high performance supercritical fluid chromatography quantitative results were in accordance with the ultra‐high performance liquid chromatography results, demonstrating the applicability of this technique for cannabinoid analysis.